Analysis of the Influence of Production and Marketing Costs on Net Profit in the Goods Industry (Food & Beverage) Listed on the Indonesia Stock Exchange - Regina Regina; Irwandi Irwandi; Ananda P (PINISI Discretion Review, 2023)
the company's net income. Net income is very important for a company. Net profit is a measure of the success of a company. Because profits help us understand our progress and commitment to shareholders. Net income also allows you to see if your goals and objectives have been achieved. Production costs and marketing costs are one indicator of the formation of company profits. The research population consists of consumer goods (food and beverage) industrial companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2020. The opulation of food and beverage industry companies is 30 companies, and the sample is 17 companies. Food and Beverage Company is a manufacturing company, namely a processing industry that processes raw materials into semi-finished goods or finished goods. Manufacturing companies are identical with factories that use machines, equipment and labor. The costs incurred by manufacturing companies include production costs. The purpose of the manufacturing company itself is to obtain the maximum net profit. The data used in this study is secondary data. The samples used in this study are the financial statements of income and notes to the financial statements of Manufacturing Companies in the Food and Beverage Subsector listed on the IDX for the 2018-2020 period.